Probing Stemness and Neural Commitment in Human Amniotic Fluid Cells - Jezierski, Anna; Gruslin, Andree; Tremblay, Roger; Ly, Dao; Smith, Cathie; Turksen, Kursad; Sikorska, Marianna; Bani-Yaghoub, Mahmud (Stem cell reviews, 2010)
Recently, human amniotic fluid (AF) cells have attracted a great deal of attention as an alternative cell source for transplantation and tissue engineering. AF contains a variety of cell types derived from fetal tissues, of which a small percentage is believed to represent stem cell sub-population(s). In contrast to human embryonic stem (ES) cells, AF cells are not subject to extensive legal or ethical considerations; nor are they limited by lineage commitment characteristic of adult stem cells. However, to become therapeutically valuable, better protocols for the isolation of AF stem cell sub-populations need to be developed. This study was designed to examine the molecular components involved in self-renewal, neural commitment and differentiation of AF cells obtained at different gestational ages. Our results showed that, although morphologically heterogeneous, AF cells derived from early gestational periods ubiquitously expressed KERATIN 8 (K8), suggesting that the majority of these cells may have an epithelial origin. In addition, AF cells expressed various components of NOTCH signaling (ligands, receptors and target genes), a pathway involved in stem cell maintenance, determination and differentiation. A sub-population of K8 positive cells (<10%) co-expressed NESTIN, a marker detected in the neuroepithelium, neural stem cells and neural progenitors. Throughout the gestational periods, a much smaller AF cell sub-population (<1%) expressed pluripotency markers, OCT4a , NANOG and SOX2 , from which SOX2 positive AF cells could be isolated through single cell cloning. The SOX2 expressing AF clones showed the capacity to give rise to a neuron-like phenotype in culture, expressing neuronal markers such as MAP2, NFL and NSE. Taken together, our findings demonstrated the presence of fetal cells with stem cell characteristics in the amniotic fluid, highlighting the need for further research on their biology and clinical applications.